Testing a rapid climate change adaptation assessment for water and sanitation providers in informal settlements in three cities in sub-Saharan Africa - Heath, Tom; Parker, Alison; Weatherhead, E. K. (International Institute for Environment and Development, 2012)
Climate change is expected to affect the poor in low- and middle-income countries most, particularly in the next few decades, through increased flooding and droughts. A very large number of these poor live in informal urban settlements, where they rely on water kiosks and pit latrines and where there is usually inadequate provision for drainage. Despite an abundance of publications on climate change, there is little advice that is specific to those providing water and sanitation services to the urban poor in these countries. This paper presents a Rapid Climate Adaptation Assessment (RCAA) for water and sanitation providers that generates recommendations on climate proofing for local service providers, utilities and local governments. Overall, the RCAA converts regional climate predictions into recommendations for local adaptations. The methodology was developed through fieldwork with communities in Lusaka (Zambia), Naivasha (Kenya) and Antananarivo (Madagascar). The paper describes the methodology, summarizes the results of its application (and the implications for adaptation) and discusses its wider application and limitations. In most cases, the proposed adaptations are not new actions, and could be described as “good water management”.